Digital Citizenship Development Model in Citizenship Education Learning - Rumiati, Sri; Karim, Aim Abdul; Darmawan, Cecep; Fitriasari, Susan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
. This research aims to find a model for the development of digital citizenship in PKn learning. This writing method uses a descriptive-analytical method, describing the things that are analyzed and discussed comprehensively and integrally. The techniques used to collect data were carried out through observation, interviews and literature studies. The results of the study show that digital citizenship is the knowledge and skills used to use technology appropriately in the digital world, manage existing risks, and take advantage of the opportunities offered by the digital world appropriately and wisely. This research concludes that there are nine elements that together form digital citizenship, namely digital access, digital commerce, digital communication, digital literacy, digital ethics, digital law, rights and obligations of digital citizens, digital health and fitness, and digital security.